Ultrasound-guided suprascapular nerve block with lidocaine vs. saline combined with physical exercises for the rehabilitation of supraspinatus tendinitis: a randomized double-blind controlled trial - Otani, Pericles Tey; Rached, Roberto Del Valhe Abi; Alfieri, Fabio Marcon; de Azevedo Neto, Raymundo Soares; Hsing, Wu Tu; Battistella, Linamara Rizzo; Imamura, Marta (Frontiers in Pain Research, 2024)
IntroductionShoulder pain is the third leading cause of musculoskeletal complaints in primary care clinics. Its prevalence varies from 14% to 34%. Among all the structures that can cause shoulder pain, the most vulnerable to injury is the tendon of the supraspinatus muscle. The ideal management protocol is still unknown. To date, little is known in the literature about the use of ultrasound-guided suprascapular nerve block as a treatment for supraspinatus muscle tendinitis. Our objective was to assess the effects of the association of a single ultrasound-guided suprascapular nerve block combined with home-based rotator cuff exercises to reduce pain and improve shoulder functioning in patients with supraspinatus tendinitis.MethodsWe evaluated the effect of a single ultrasound-guided suprascapular nerve block on pain and functioning of people with supraspinatus tendinitis. Diagnosis was performed using the positive Jobe test. Due to large disparity between clinical and radiological findings, only clinical diagnostic criteria were used to select patients. This was a double-blind, randomized, controlled, clinical study in which patients in the intervention group (n = 42) received a single injection of 5 ml of 2% lidocaine, while in the control group (n = 41) patients underwent the same procedure receiving saline solution 0.9%. All patients received face to face instructions by an experienced physiotherapist and a leaflet explaining home-based exercises. Pain and functioning were assessed using the Shoulder Pain and Disability Index (SPADI) questionnaire before the procedure, one week and 12 weeks after the procedure.ResultsPatients in both groups improved significantly since the initial evaluation until the 12th week. Intervention group SPADI (pre, 1 week, 12 weeks): 75.80 ± 18.96, 56.25 ± 31.37, 46.31 ± 31.41 (p < 0.001); Control group SPADI: 75.49 ± 16.67, 50.51 ± 27.58, 49.37 ± 30.90 (p < 0.001). However, there were no significant differences between groups (p = 0.291).Discussion/conclusionWe concluded that both lidocaine and saline ultrasound-guided suprascapular nerve blocks reduce pain and improve shoulder functioning in patients with supraspinatus tendinitis. Unexpectedly, the same block performed with saline showed similar results and effects. Clinical Trial RegistrationClinicalTrials.gov, identifier [NCT02495818].